2016
DOI: 10.1177/1098612x16636419
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography, radiology and echocardiography in cats naturally infected with Aelurostrongylus abstrusus

Abstract: Objectives The aims of the study were to describe the radiographic and computed tomographic features in cats naturally infected with Aelurostrongylus abstrusus, and to identify signs of pulmonary hypertension with echocardiography. Methods Fourteen cats positive on Baermann test for A abstrusus were included in the study. All cats underwent thoracic radiography, CT and echocardiography. Results The most common clinical signs were coughing (10/14) and dyspnoea (5/14). Radiographic findings included a generalise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
31
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 22 publications
9
31
1
Order By: Relevance
“…The radiographic finding indicates a chronic process with mild changes on the diaphragmatic lobes. Similar data are found in the literature, since the radiographic findings depends on the degree of lung damage (Lacava et al, 2017). Since in the presented case there were no respiratory symptoms or disseminated lung lesions determined by a radiographic examination, it was concluded that in this case chronic and subclinical aelurostrongylosis was diagnosed.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The radiographic finding indicates a chronic process with mild changes on the diaphragmatic lobes. Similar data are found in the literature, since the radiographic findings depends on the degree of lung damage (Lacava et al, 2017). Since in the presented case there were no respiratory symptoms or disseminated lung lesions determined by a radiographic examination, it was concluded that in this case chronic and subclinical aelurostrongylosis was diagnosed.…”
Section: Discussionsupporting
confidence: 89%
“…Lung lesions are localized in diaphragm lobes, and the bronchial wall is thickened, indicating the existence of a mixed pattern of lung lesion. For more intensive infections with A. abstrusus radiography shows generalized interstitial lesions in the lungs of affected cats (Lacava et al, 2017). Additionally, the detected changes in the lung lobe in our case are specific to verminous bronchopneumonia.…”
Section: Discussionsupporting
confidence: 57%
“…In particular in our case the right caudal lobe was more affected than the left lung lobe. Little information is available regarding bronchial changes in feline dirofilariasis and only recent studies reported on the CT features of the airways in cats experimentally infected with D. immitis and naturally and experimentally infected cats with Aelurostrongylus abstrusus …”
Section: Discussionmentioning
confidence: 99%
“…Thoracic radiography should be the first assessment in patients with a suspect of lower airway and pulmonary parenchyma disorders. The most common abnormalities detected on chest radiographs in naturally ( 31 , 38 , 39 ) or experimentally ( 40 ) infected cats with lungworm infection are bronchial, nodular, and unstructured interstitial pattern with a multifocal distribution, evolving into a generalized alveolar pattern in severe cases. However, these data relate to A. abstrusus or mixed lungworm infections, and information on imaging features of troglostrogylosis is scant.…”
Section: Diagnosismentioning
confidence: 99%